The Circular Economy: Case Studies About the Transition From the Linear Economy - Ncibi, Chaker (Academic Press, 2019)
"The Circular Economy: Case Studies about the Transition from the Linear Economy explores examples of the circular economy in action. Unlike other books that provide narrow perceptions of wide-ranging and highly interconnected paradigms, such as supply chains, recycling, businesses models and waste management, this book provides a comprehensive overview of the circular economy from various perspectives. Its unique insights into the approaches, methods and tools that enable people to make the transformation to a circular economy show how recent research, trends and attitudes have moved beyond the ""call to arms"" approach to a level of maturity that requires sound scientific thinking. Compiles evidence through case studies that illustrate how individuals, organizations, communities and countries are transitioning to a circular economy Provides a theoretical and empirical summary of the circular economy that emphasizes what others are actually doing and planning Highlights achievements from industry, agriculture, forestry, energy, water and other sectors that show how circular principles are applicable, eco-friendly, profitable, and thus sustainable".
Keywords: Sustainable development; Economics; Développement durable; Économie politique; sustainable development; economics